Revealing students' numeracy ability: A case study on word problems in junior high school - E. Epran; Jarnawi Afghani Dahlan; Yaya Sukjaya Kusumah (Universitas Muhammadiyah Malang, 2025)
This study explores students' numeracy ability in solving mathematical word problems. A qualitative approach with a descriptive method was employed to provide an in-depth depiction of students' numeracy levels. The research utilized a case study design involving 16 eighth-grade students from a junior high school in Bandung City as subjects. Data collection techniques included a numeracy test to measure students' ability to solve mathematical word problems and interviews to validate the test results and further investigate students' thought processes. The findings revealed a variation in students' numeracy ability. A total of 25% of the students (4 students) had low numeracy ability, while 37.5% (6 students) demonstrated moderate numeracy ability, and 37.5% (6 students) showed high numeracy ability. Additionally, the average numeracy score was 70.625, indicating that, overall, students' numeracy ability falls into the 'good' category. These findings underscore the importance of implementing learning approaches that support the development of numeracy, particularly in the context of mathematical word problems.